Level of challenges in accounting records management in digital collection transactions of small-medium enterprises (smes) in Sampaloc Manila - Bautista, Kryztal Glance; Centino, Bianca Charlotte; Donato, Eouj Oliver; Santos, Catherine Josh; Villegas, Donita Joy (Manila : National University, 2023)
This study aims to identify the level of challenges in accounting records management in digital collection transactions in small enterprises business in Sampaloc Manila.
Chapter 1. The problem and its background -- Chapter 2. Review of related literature -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.
Keywords: DIGITAL COLLECTION SYSTEM; ACCOUNTING RECORDS MANAGEMENT